Optimizing Farmers' Income through Digital Innovation in Agricultural Supply Chains: English - Sri Maitri, Wayan; Widhya Sedana Putra P, Komang; Ni Wayan Lasmi (GIAT : Teknologi untuk Masyarakat, 2025)
Agriculture plays a very vital role in the development of the rural economy; nevertheless, a large number of farmers are found to be confronted with financial crises due to changes in market prices, inefficient practice, or a very poor awareness of modern technologies. Equipping farmers with up-to-date digital innovations along the value chain focuses on sustainable farming practices, financial literacy, and digital marketing strategies to maximize income. The general vision is to increase farmers’ productivity, profitability, and resilience by equipping them with knowledge that will enable to adapt to changing markets. Participatory approaches involve farmers in workshops and field demonstrations of sustainable agriculture, digital marketing, and financial management. Farmers learn how to manage their farms more effectively by developing their e-commerce platformto market their products, using social media to access broader markets, and applying precision farming techniques. The program participants witnessed improved incomes for the farmers, enhanced access to markets, enhanced financial management, and an improvement in agricultural productivity. Application of the digital tool supported the introduction of sustainable farming practices, therefore, contributing to economic resilience in the long term, as well as environmental sustainability.